1997
DOI: 10.1152/ajplung.1997.273.1.l185
|View full text |Cite
|
Sign up to set email alerts
|

Systemic blood loss affects NF-kappa B regulatory mechanisms in the lungs

Abstract: The nuclear regulatory factor (NF)-kappa B is activated in the lungs of patients with acute respiratory distress syndrome (ARDS). In experimental models of acute lung injury, activation of NF-kappa B contributes to the increased expression of immunoregulatory cytokines and other proinflammatory mediators in the lungs. Because of the important role that NF-kappa B activation appears to play in the development of acute lung injury, we examined cytoplasmic and nuclear NF-kappa B counterregulatory mechanisms in lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 0 publications
1
13
1
Order By: Relevance
“…The ability of NAC supplementation to prevent priming in this model is similar to that previously reported for CINC expression and implies that oxidant stress generated during hemorrhage/resuscitation is a significant contributor to the induction of the primed state. Studies by other investigators suggest that xanthine oxidase produced after ischemia/reperfusion may be primarily responsible for elaboration of these oxidants (50)(51)(52). A recent report demonstrated that upregulation of inducible nitric oxide synthase during the shock phase of shock/ resuscitation may be essential to the development of lung injury, a finding consistent with a conclusion that cellular events occurring during the hypoxic phase may also contribute to the primed state (53).…”
Section: Discussionsupporting
confidence: 59%
“…The ability of NAC supplementation to prevent priming in this model is similar to that previously reported for CINC expression and implies that oxidant stress generated during hemorrhage/resuscitation is a significant contributor to the induction of the primed state. Studies by other investigators suggest that xanthine oxidase produced after ischemia/reperfusion may be primarily responsible for elaboration of these oxidants (50)(51)(52). A recent report demonstrated that upregulation of inducible nitric oxide synthase during the shock phase of shock/ resuscitation may be essential to the development of lung injury, a finding consistent with a conclusion that cellular events occurring during the hypoxic phase may also contribute to the primed state (53).…”
Section: Discussionsupporting
confidence: 59%
“…In hyperoxia, increased NF-κB activation is one of the first pulmonary responses upon exposure, and this activation occurs before the detection of any proinflammatory cytokine increases [74,[138][139][140][141]. The NF-κB-binding motif is present in the promoter regions of many genes that encode proinflammatory cytokines [81,[142][143][144].…”
Section: Transcription Factors and Proinflammatory Cytokines In Hypermentioning
confidence: 99%
“…Circulating endotoxin has been linked to the development of ALI in critically ill patients and, in experimental settings, endotoxemia results in the development of ALI (4). Similarly, hemorrhage, as a model for trauma-induced blood loss, also produces ALI (5)(6)(7). Neutrophils are an important contributory factor in the development of ALI, since the severity of pulmonary injury is decreased when neutropenia is present (8).…”
Section: Introductionmentioning
confidence: 99%